Effect of Adding Homeopathy to the Routine Treatments of Veterans with Chronic Depression - S.A. Mahmoudian; Gh.R. Kheirabadi; M.R. Meracy (Afarand Scholarly Publishing Institute, 2015)
Aims: Many psychiatrists in treating patients with chronic depression, in addition to conventional and psychological treatment turned to the use complementary therapies such as homeopathy. This study aimed to investigate the effectiveness of adding homeopathy to common depression treatments on depression severity and quality of life of depressed veterans.  Materials & Methods: This randomized double-blind clinical trial was done on 65 depressed with symptoms similar to Natrium muriaticum hospitalized in Shahid Rajai Hospital of Isfahan in 2012-13. patients randomly assigned into two groups of homeopathy (n=35) and control (n=30) groups. homeopathy group in addition to conventional therapy received homeopathic medicine and placebo administrated for control group. Patients completed the Beck Depression Inventory and Quality of Life Questionnaire before and after the intervention. Data were analyzed by SPSS 20 software with Mann-Whitney and covariance tests.  Findings: Mean depression scores (p=0.577) and quality of life (p=0.524) was not significantly different after intervention (by controlling the severity of depression and quality of life before the intervention) was not different between two groups, but there was a  significant difference between two groups in physical and mental domains of quality of life (p<0.05). Conclusion: 6 months homeopathic treatment of chronic depressed veterans depression was not is not effective, but it is effective on their mental and physical aspects of quality of life.